Detection of reactive nitrogen containing particles in the tropopause region – evidence for a tropical nitric acid trihydrate (NAT) belt - C. Voigt; H. Schlager; A. Roiger; A. Stenke; M. de Reus; S. Borrmann; E. Jensen; C. Schiller; P. Konopka; N. Sitnikov (Atmospheric Chemistry and Physics, 2008)
The detection of nitric acid trihydrate (NAT, HNO3×3H2O) particles in the tropical transition layer (TTL) harmonizes our understanding of polar stratospheric cloud formation. Large reactive nitrogen (NOy) containing particles were observed on 8 August 2006 by instruments onboard the high altitude research aircraft M55-Geophysica near and below the tropical tropopause. The particles, most likely NAT, have diameters less than 6 μm and concentrations below 10-4 cm−3. The NAT particle layer was repeatedly detected at altitudes between 15.1 and 17.5 km over extended areas of 9.5 to 17.2° N and 1.5° W to 2.7° E above the African continent. Satellite observations suggest that the NAT particles could have nucleated on ice fed by convective activity. Once nucleated, the NAT particles can slowly grow within the TTL for days, while being transported over long distances. Their in-situ detection combined with global model simulations of the NAT supersaturation near the tropical tropopause indicate the potential for a tropical tropopause NAT particle belt.